Epstein-Barr Virus–Associated B-Cell Lymphoproliferative Disorder Involving the Adrenal Gland in Granulomatosis With Polyangiitis - Indira Acharya; Lanaya Williams Smith; Stuart Mitchell Levine; Huaibin Mabel Ko; Govind Bhagat; Christopher J. Haas (Annals of Internal Medicine: Clinical Cases)
Epstein-Barr virus (EBV)–associated lymphoproliferative disorders (LPDs) are rare conditions. Immunomodulatory therapies impair T-cell–mediated immune responses to latent EBV-infected memory B cells, promoting their reactivation and leading to the excessive division of infected cells, which can result in the development of EBV-associated lymphocyte proliferations. Lymphoproliferative disorders related to immunomodulatory agents are recognized as potential life-threatening complications of prolonged immunomodulator administration. Methotrexate-associated LPDs in rheumatoid arthritis and azathioprine-associated LPDs in inflammatory bowel disease have been reported previously. To our knowledge, we report a unique and possibly the first documented case of a B-cell LPD, specifically an EBV-associated polymorphic LPD, involving the adrenal gland in a patient with granulomatosis with polyangiitis treated with azathioprine.